Incidence of Hepatitis B Surface Antigen (HBsAg) Infection and Its Relationship with Risk Factors at Janitors at Regional General Hospital dr. M. M. Dunda Limboto Gorontalo - Indra Elisabet Lalangpuling; Zumrotul Abidah Dakio; Nikma Nikma; Dwi Setiyo Prihandono; Lendawati Lendawati (Universitas Nahdlatul Ulama Surabaya, 2023)
Hepatitis B is an inflammatory liver disease caused by the Hepatitis B virus, which can be acute or chronic. The outer membrane protein of Hepatitis B Virus (HBV) is known as Hepatitis B Surface Antigen (HBsAg). Janitors are employees who are tasked with cleaning the hospital environment to keep it clean, because of the the dangers that exist in hospitals, such as disease transmission, can occur if the hospital environment is not kept clean. The purpose of this study was to describe the results and their relationship to risk factors of the Hepatitis B examination on janitors at the Regional General Hospital (RSUD) dr. Mansyoer Mohammad Dunda Limboto Gorontalo. This study used a descriptive method with an accidental sampling technique. The sample in this study amounted to 33 respondents who met the inclusion criteria. Specimen were examined using the rapid test method. The data were presented descriptively and statistically to see the relationship between work and the incidence of Hepatitis B infection. The results obtained were as many as 33 respondents by conducting an HBsAg examination, with the results obtained being 2 reactive people and 31 non-reactive people. The results of statistical tests on the relationship between infection status and age showed a p-value of 0.019 and the relationship between infection status and symptoms showed a p-value of 0.002. The study’s findings revealed that there was a substansial correlation between the respondents’ reported symptoms and their infection status (6% of respondents teste for Hepatitis B).